Ludowi wizjonerzy w Polsce XVI-XVII w.: Jan Mikosz, Jakub Ruszczyk i Tomasz Michałek - Wiślicz, Tomasz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny)
The paper proposes employing a biographical approach in studies on popular piety in early modern (16th and 17th century) Poland. Using broadened category of egodocument and based on text of ecclesiastical provenance, the text presents biographies of three visionaries of sources origin who in 16th and 17th century allegedly experienced Marian apparitions
Keywords: Marian apparition; visionaires; popular piety; egodocuments; miraculous places